2018
DOI: 10.1159/000486175
|View full text |Cite
|
Sign up to set email alerts
|

Using the Capture-Recapture Method to Estimate the Incidence of Amyotrophic Lateral Sclerosis in Beijing, China

Abstract: Background: To assess the total, gender-related and ageing process-related incidence rates of amyotrophic lateral sclerosis (ALS) in Beijing, China. Determine whether the decreased male to female ratio among postmenopausal age groups. Methods: We used the 2-source capture-recapture method to estimate the incidence of ALS in Beijing. The primary and secondary data sources were from diagnostic hospitals and assisted care institutions in the same area from 2010 to 2015. Results: A total of 562 cases and 283 cases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 18 publications
(28 reference statements)
2
3
0
Order By: Relevance
“…This finding indicates that the incidence and prevalence are similar across countries in East Asia, and are independent of the Sociodemographic Index (SDI), consistent with the meta-analysis of the Global Burden of Disease Study 2016 2. The prevalence of ALS in our study was comparable with the findings from Hong Kong and Taiwan, but the incidence seemed to be higher than in these two regions and than that reported in two studies in mainland China 5 8 10 11. Our large national sample size and standardised rate calculation methodology ensured relatively stable and new results10 11 28; these results indicated that the actual number of incident patients with ALS in Asia was still higher than that in Western populations given the large population.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…This finding indicates that the incidence and prevalence are similar across countries in East Asia, and are independent of the Sociodemographic Index (SDI), consistent with the meta-analysis of the Global Burden of Disease Study 2016 2. The prevalence of ALS in our study was comparable with the findings from Hong Kong and Taiwan, but the incidence seemed to be higher than in these two regions and than that reported in two studies in mainland China 5 8 10 11. Our large national sample size and standardised rate calculation methodology ensured relatively stable and new results10 11 28; these results indicated that the actual number of incident patients with ALS in Asia was still higher than that in Western populations given the large population.…”
Section: Discussionsupporting
confidence: 87%
“…The prevalence of ALS in our study was comparable with the findings from Hong Kong and Taiwan, but the incidence seemed to be higher than in these two regions and than that reported in two studies in mainland China 5 8 10 11. Our large national sample size and standardised rate calculation methodology ensured relatively stable and new results10 11 28; these results indicated that the actual number of incident patients with ALS in Asia was still higher than that in Western populations given the large population. In addition, men were more likely to have ALS than females, with a 1.4-fold increased risk, a finding consistent with previous studies in Asian and other races 1 7 29–31…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Capture–recapture is a widely used statistical technique that examines the overlap in identification of cases from data sources and uses this information to estimate the number of cases who were not identified by any of the sources, thus enabling a conclusion about the completeness of ascertainment ( 27 ). Capture–recapture method has also been used by other studies across different race and ethnic background to correct for the missing cases in the estimations of incidence rates ( 28 30 ). For the purposes of estimating the degree of under-ascertainment by the Registry data source, Nelson et al applied capture–recapture methods to the 15,927 cases identified by the three data sources during the registry year 2014 ( 31 ).…”
Section: Methodsmentioning
confidence: 99%